EKSPLORASI PERSEPSI PUBLIK TERHADAP ANCAMAN KECERDASAN BUATAN PADA EKSISTENSI TENAGA KERJA: Studi Netnografi Diskusi Youtube - Suyitno (ECO-BUILD, 2026)
Artificial intelligence (AI) has become a highly influential technology in the transformation of the world of work, bringing significant changes to the job structure and skills needed in various sectors. This study aims to explore the public perception of the threat posed by AI to the existence of the workforce, focusing on analyzing public discussions on the YouTube platform through a netnography approach. The results show a tension between optimism about AI's potential to improve efficiency and concerns about its negative impact on human work. Most respondents expressed the view that AI can replace routine work, but also create new opportunities that require technical skills and adaptation. This difference in perception is also influenced by the level of knowledge and experience of users towards technology. The study emphasizes the importance of retraining and skills development policies to ensure the workforce can adapt to the changes brought about by AI. It also found that inequality in access to technology and inequality in the distribution of AI benefits can exacerbate social and economic disparities between developed and developing countries.